Impact of Socio-economic Status on Language Learning Motivation of Secondary School Students - Singh, Rajni; Sanjiv Kumar Choudhary (JOURNAL OF INDIAN EDUCATION, 2016)
Many social factors are likely to affect the affective factors such as motivation indirectly affecting the learning of English as a second or foreign language. This study examined the influence of Socio-economic Status (SES) on students’ Language Learning Motivation (LLM). We conducted a survey by using questionnaire to collect information about SES of the students and motivation. The respondents were students of secondary schools (Class X) affiliated to Central Board of Secondary Education. The data analyses were done using SPSS by descriptive statistics, anova and simple linear regression. SES comprises fathers’ education, mothers’ education, fathers’ occupation, mothers’ occupation and family income. LLM construct included integrativeness and attitude towards learning situation developed by Gardner (1985). The reliability of the questionnaire for SES and LLM was found to be α=0.735 and α=0.608 respectively. Results indicated that there is a significant relationship between SES and language learning motivation which reflects that increase in social status leads to increase in language learning motivation.